Sistem Kontrol yang Terbentuk Pada Tradisi Sarang di Desa Kejawan Kabupaten Bondowoso - Elia Nur Fadillah; Fatihatul Firdaus; Lusiana Agustiningtiyas (Institut Nalanda, 2023)
Every community has its own uniqueness in forming a tradition. The Sarang Tradition in Kejawan Village refers to the custom that is carried out continuously which then become a tradition that is always done by the local community when they are going to hold an event. The objective of this research is to investigate more deeply about the Sarang Tradition in Kejawan and its impact on the status of Tokang Sarang within the community. By using qualitative research method and conducting observation, interview, as well as using documentation as the data collection methods, it was known that the Sarang ritual in Kejawan has differences compared to rain repelling rituals in other regions. The implementation of Sarang ritual includes the recitation of the holy Quran and Shalawat, and the use of Blackstone (hajar aswad). If there are any mistakes during the process, then, the rain repelling ritual will not work as planned and it will also affect the ability and the community’s perception of Tokang Sarang. Tokang Sarang is required to do some other rituals to maintain their abilities from fading and to make them stronger. They hold power over the area they control and they also have a significant position within the community.